Like, Share, Lead: The Impact of Social Media on Authority and Legitimacy in the Labor Movement - Mark Friis Hau (Social Media + Society)
This article draws on the theories of Max Weber to explore how social media can redefine organization and hierarchy in the contemporary labor movement. Through a mixed-methods approach combining quantitative analysis of social media posts and in-depth interviews with key grassroots activists in Denmark, the article highlights how the personal, affective, and participatory nature of social media challenges traditional union legitimacy. The findings suggest that as affect and individual narratives become increasingly powerful tools for the labor movement, unions must explore ways to incorporate these new modes of communication. This includes a deep understanding of the interplay between different forms of legitimacy on digital platforms, and how these can complement each other rather than compete in the pursuit of labor rights and democratic organization. This study contributes to a broader discussion on the impact of digital platforms on organizations, offering a unique perspective on the intersection of technology and power.